Keputusan Pembelian Minuman Penambah Energi Extra Joss ditinjau dari Peran Kekuatan Citra Merek dan Penetapan Harga Produk - Tri Seno Anjanarko; Didit Darmawan (Forum Kerjasama Pendidikan Tinggi, 2023)
There are various types of beverage products that are traded in the market, such as mineral water, soft drinks, or energy drinks. One of the energy-boosting drink brands sold in Indonesia is Extra Joss. Extra Joss is the first energy drink in powder form in Indonesia. In its development, more and more energy-boosting drink brands emerged which became competitors to Extra Joss. Research was conducted to determine the effect of brand image and price on purchasing decision making. The object of research is construction workers who are active in projects that are taking place in the city of Surabaya. Sampling was done by means of purposive sampling. The researcher distributed 100 questionnaires, but the questionnaires returned to the researchers were 79 questionnaires which were used as the number of samples. Multiple linear regression analysis was used in this study. The finding shown is that brand image has a significant effect on the purchasing decision of Extra Joss energy drink. Apart from that, the decision to buy Extra Joss energy drink is also significantly influenced by price. Brand image and price have a significant effect on the purchasing decision of Extra Joss energy drink.